Spratly Island dispute: Malaysia's perspective / Muhamad Razman Sahat ... [et al.] - Sahat, Muhamad Razman; Jamal, Muhammad Amirul Arif; Ahmad Effendi, Ahmad Qayyum Razzirullah; Hashim, Amir Sharifuddin (2013)
This research is regarding the disputes in the Spratly Island. The disputes in this area arose when the nations surrounding the area put up the claim on some part of the archipelago. The country that put up the claim on this archipelago is People's Republic of China, Vietnam, Malaysia, Philippines, Brunei and Republic of China (Taiwan). This archipelago became an issue of claim as it contains much significance that can gear up the economy and political power of the nation involve. In order to prevent this dispute from turning into arms conflict, peaceful dispute settlement needs to be applied. One of the peaceful dispute settlements that can be use is United Nation Convention on Law of Sea 1982 that are going to discuss further in this research. Under UNCLOS 1982, the law of Exclusive Economic Zone (EEZ) can be applied to solve this dispute. The law of EEZ alone cannot resolve this dispute when it comes to the overlapping claim. Thus, the decision in the previous case regarding the area dispute such as the case Island of Palmas are also going to be applied in this research to overcome this lacunae. Besides that, this research also will suggest any possible peaceful dispute settlement that is available in order to resolve these issues.